How to lead by the book : proverbs, parables, and principles to tackle your toughest business challenges - Anderson, Dave, 1961- (Wiley, 2011)
"Biblical solutions to dozens of the toughest challenges leaders face today. Concise, to-the-point, and highly useable, How to Lead by THE BOOK presents a series of personal and business challenges recognizable to leaders, then deals with each through insight, personal experience, and a discussion of why conventional approaches often fail. Each section then concludes with winning proverbs, parables, or principles that offers applicable strategies to solve the issue. In this practical and inspiring guide, you'll discover proven methods and advice to shape young leaders, stretch veteran leaders, become a better communicator, maintain your work-life balance, deal with dishonesty among competitors, and much more. Shows why typical approaches to leadership problems often fail, while biblical wisdom succeeds Covers both day-to-day dilemmas and larger questions of management, accountability, and vision From the bestselling author of How to Run Your Business by THE BOOK, Up Your Business, and If You Don't Make Waves Youll Drown What is the number one downfall for leaders? When is the best time to make a decision? How do you hold others accountable? How do you survive success with your principles intact? What does the Bible say about time management? Get the answers to these and many more practical business questions when you discover the winning wisdom of How to Lead by THE BOOK."--